PROSPECTS FOR THE DEVELOPMENT OF FISH PRODUCTION - Ergashev, Rakhmatulla Khidirovich; Beglayev, Uchkun Khurramovich (The journal of contemporary issues in business and government, 2021)
The article presents research and data on the development parameters of the national economic situation of the country, the creation of a stable economic system and the current state of fisheries and the forecast parameters until 2025 for its further development.